Comparison of endoscopic and open resection of sinonasal squamous cell carcinoma: a propensity score–matched analysis of 652 patients. Issue 3 (6th December 2017) - Kılıç, Suat; Kılıç, Sarah S.; Baredes, Soly; Chan Woo Park, Richard; Mahmoud, Omar; Suh, Jeffrey D.; Gray, Stacey T.; Eloy, Jean Anderson
Abstract : Background: The use of endoscopic resection as an alternative to open surgery for sinonasal malignancies has increased in the past 20 years. Methods: The National Cancer Database was queried for cases of sinonasal squamous cell carcinoma (SNSCC) without cervical or distant metastases that were treated surgically between 2010 and 2014. They were split into 2 groups based on surgical approach: open or endoscopic. Demographics, facility and insurance type, stage, tumor characteristics, postoperative treatment, 30‐day readmission rate, 30‐ and 90‐day mortality, and overall survival (OS) were compared between the 2 groups. Cox proportional hazard analysis was performed. Propensity score matching (PSM) was used to mimic a randomized, controlled trial. Results: A total of 1, 483 patients were identified: 353 (23.8%) received endoscopic and 1130 (76.2%) received open surgery. Age, gender, race, geographic region, tumor size, surgical margins, postoperative chemoradiation, and 30‐day readmissions did not vary significantly between the 2 groups. Open surgery was more common in academic centers (62.8% vs 54.2%; p = 0.004), less common for tumors of the ethmoid and sphenoid sinus ( p < 0.0001), less common for stage IVB tumors, and associated with longer hospital stay (mean, 4.67 days vs 2.50 days; p < 0.0001). Five‐year OS (5Y‐OS) was not significantly different between the 2 approaches ( p = 0.953; open: 5Y‐OS, 56.5%; 95% confidence interval, 51.3% to 61.6%; endoscopic: 5Y‐OS, 46.0%; 95% confidence interval, 33.2% to 58.8%). In the PSM cohort of 652 patients, there was also no significant difference in OS ( p = 0.850). Conclusion: Endoscopic surgery is an effective alternative to open surgery, even after accounting for confounding factors that may favor its use over the open approach. It is also associated with a shorter hospital stay.